THE ROLE OF ASSIGNMENT TEACHERS IN IMPROVING ARABIC LANGUAGE COMPETENCE IN SANTRI AT THE RAUDHATUL ULUM ISLAMIC BOARDING SCHOOL DORMITORY LPBA JEMBER - Qudsy, Muhowwifullah Amin; Wijaya, Muallim (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to describe the role of task teachers in improving students' foreign language competence in everyday life. The research methodology used is qualitative with a case study approach. The research data were collected using in-depth interview and observation techniques. The subjects of the study included 17 students. The results of this study indicate that the role of the task teacher is very important in improving the foreign language competence of students who can build skills in the fields of listening, speaking, writing and reading. As well as the role of the task teacher can provide constructive feedback for students about their Arabic language skills.